The Integration Of Grammar In English Language Teaching: A Study Of Hebei University Efl Teachers’ Beliefs And Practices - Hongmei, Han (2013)
This study focuses on teachers’ beliefs and practices in relation to the grammar teaching in Chinese EFL context. The objectives of the study are to explore Chinese EFL teachers’ beliefs about grammar and grammar teaching, to examine classroom practices that characterize teachers’ grammar teaching approach, to investigate the impact of educational experiences, professional experiences and contextual factors on teachers’ beliefs and practice with reference to grammar teaching. Participants of the study were six in-service EFL teachers working at Hebei University in China. The data in this study were obtained through interviews, classroom observations, stimulated recalls and teachers’ feedback on students’ compositions. The findings of the study indicate that teachers held positive beliefs about grammar and grammar teaching in EFL teaching context. However, several inconsistencies were identified between teachers’ beliefs and classroom practices. In addition, the research data reveal that teacher’s beliefs and practices with reference to grammar teaching were shaped by educational and professional experiences. The data also indicate that teachers’ beliefs and practices were influenced by specific contextual factors, including limited instruction time, syllabus, tests, student factors, computer and internet-based teaching reform and so on. This study provides EFL teachers with insights into teaching through which they can reflect on their beliefs and improve instructional practices. It also addresses a need for teacher educators to facilitate teacher development through the innovation of teacher training programs